THE SIMULATION OF THE SHIELDING COATINGS WITH THE ABILITY OF THE REFLECTED RADIATION INTERFERENCE QUENCHING IN ULTRAVIOLET WAVELENGTH RANGE - T. M. Pechen; A. M. Prudnik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The goal of simulation consisted in studying of ways of minimization of the function describing spectral reflectivity of the shielding coatings. The results of the simulation of the coatings having interference suppression property of the reflected rays in a wavelength range from 250 to 600 nm. The simulation realized in the program EMTL, allowed to determine: the thickness of shielding coating in the ultraviolet (UV) region is directly dependent on the function describing the spectral reflectance of the film. The comparative analysis of the shielding coatings based on aluminum oxide, magnesium fluoride and titanium dioxide is represented.